2015
DOI: 10.1089/apc.2015.0122
|View full text |Cite
|
Sign up to set email alerts
|

Depression and HIV Serostatus Disclosure to Sexual Partners Among Newly HIV-Diagnosed Men Who Have Sex with Men

Abstract: HIV disclosure to sexual partners facilitates joint decision-making and risk reduction strategies for safer sex behaviors, but disclosure may be impacted by depression symptoms. Disclosure is also associated with disclosure self-efficacy, which in turn may also be influenced by depressive symptoms. This study examined the relationship between depression and HIV disclosure to partners following diagnosis among men who have sex with men (MSM), mediated by disclosure self-efficacy. Newly HIV-diagnosed MSM (n = 92… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 49 publications
(54 reference statements)
0
14
1
Order By: Relevance
“…These findings are consistent with previous studies that have identified factors associated with nondisclosure of HIV, which include poor retention in care and depression. 37,38 Over the course of 28 days, men recorded 1412 days during which they engaged in condomless vaginal and anal intercourse, of which half involved nonconcordant partners. As shown in the results among men with nondisclosed nonconcordant partners, 541 of the 819 days (66%) in which they recorded sexual activity were with nonconcordant partners.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with previous studies that have identified factors associated with nondisclosure of HIV, which include poor retention in care and depression. 37,38 Over the course of 28 days, men recorded 1412 days during which they engaged in condomless vaginal and anal intercourse, of which half involved nonconcordant partners. As shown in the results among men with nondisclosed nonconcordant partners, 541 of the 819 days (66%) in which they recorded sexual activity were with nonconcordant partners.…”
Section: Discussionmentioning
confidence: 99%
“…Since the introduction of widespread antiretroviral therapy (ART), evidence on the association between non-disclosure and condom use among HIV-diagnosed MSM has been mixed; certain studies found that nondisclosure was associated with higher prevalence of condomless sex or condomless sex with HIV-serodifferent partners (CLS-D) (Cook, Valera, & Wilson, 2015;Hirsch Allen et al, 2014;Klitzman et al, 2007;Morin et al, 2005;Parsons et al, 2005;Simon Rosser et al, 2008;Wilson et al, 2016), others found no evidence of an association (Kalichman, DiMarco, Austin, Luke, & DiFonzo, 2003;Marks & Crepaz, 2001;Poppen, Reisen, Zea, Bianchi, & Echeverry, 2005;Przybyla et al, 2014;Simoni & Pantalone, 2004;van Kesteren, Hospers, van Empelen, van Breukelen, & Kok, 2007), while some reported that non-disclosure was linked to condom-protected sex (Abler et al, 2015;Klitzman et al, 2007;Serovich et al, 2018;Simon Rosser et al, 2008). Studies that examined levels of disclosure to sexual partners showed that those who disclose to some partners tend to report higher levels of condomless sex compared to those who disclose to none or most/all partners (Abler et al, 2015;Brown, Serovich, Kimberly, & Umasabor-Bubu, 2015;Durham et al, 2013;Parsons et al, 2005;Simon Rosser et al, 2008). Only two studies from the UK (2008-09) (Elford, Ibrahim, Bukutu, & Anderson, 2008;Fox et al, 2009) showed prevalence estimates of disclosure to sexual partners, but none examined associations between disclosure and condomless sex.…”
Section: Introductionmentioning
confidence: 99%
“…A substantial body of literature on the enabling and hindering factors for HIV status disclosure between MSM has been published, identifying the following factors associated with disclosure of HIV serostatus: disclosure is more likely between steady partners compared to non-steady partners; and for non-steady partners, disclosure depends on the setting where the partners have met. HIV positive status disclosure is negatively associated with perceived HIV-related stigma, depressive symptoms, and increasing age (if older than 50 years) [ 4 , 9 18 ].…”
Section: Introductionmentioning
confidence: 99%